Improving behavior of reinforced concrete frames to resist progressive collapse through steel bracings - Qian, Kai (2020)
External installation of steel braces has been proved an effective seismic strengthening or retrofitting scheme to upgrade the lateral load-resisting capacity of reinforced concrete (RC) frames. However, the effectiveness of steel bracing in improving the progressive collapse resistance potential of RC frames is vague. To fill the gap, five one-quarter-scaled specimens (one bare frame and four braced frames) were tested subject to a pushdown loading regime. The RC frames were nonseismically detailed for reference. Four braced frames with different bracing configurations were tested to evaluate the efficiency of braces for upgrading the load-resisting capacity of RC frames. A rational design method was implemented for designing the braced frames, including the connections between the braces and RC frames. Experimental results proved that steel bracing could increase the first peak load and initial stiffness of the frames significantly. Before mobilization of catenary action in RC frames, the tensile braces were fractured, but the compressive braces experienced severe buckling. Consequently, the braced specimens performed similarly to the bare frame in the catenary action stage.